2016
DOI: 10.1590/0103-6440201600600
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-resorptive Effects of Atorvastatin on Alveolar Bone Loss in Wistar Rats

Abstract: The aim of this study was to evaluate the anti-inflammatory and anti-resorptive effect of atorvastatin (ATV) in an experimental alveolar bone loss (ABL) model. Wistar rats were subjected to ligature placement around the maxillary second molar for 11 days. The animals received 0.9% saline (2 mL/kg) or ATV (0.3, 3 or 27 mg/kg) daily by gavage. ABL was evaluated by resorption area and histopathological analysis. Serum bone-specific alkaline phosphatase (BALP) activity was also evaluated. Leukogram was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Several studies have shown that this model is able to reproduce the main characteristics seen on human periodontitis, such as bone loss and destruction of periodontal ligament (Goes et al, 2010, 2016; Sousa et al, 2016) increase on oxidative stress (Di Paola et al, 2004), and exacerbation of inflammatory process (Leitão et al, 2005; Goes et al, 2012, 2016; Sousa et al, 2016), which confirm our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have shown that this model is able to reproduce the main characteristics seen on human periodontitis, such as bone loss and destruction of periodontal ligament (Goes et al, 2010, 2016; Sousa et al, 2016) increase on oxidative stress (Di Paola et al, 2004), and exacerbation of inflammatory process (Leitão et al, 2005; Goes et al, 2012, 2016; Sousa et al, 2016), which confirm our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In order to induce in ammatory bone loss, it was used the ligature-induced periodontitis model based on our previous studies [8,9,[12][13][14][15][16][17][18]23], which consists of inserting a 3.0 nylon suture thread around the upper left 2nd molar of a rat under anesthesia (80 mg/kg of Ketamine + 10 mg/kg of Xylazine, i.p.). A surgical knot was placed facing the vestibular side of the tooth.…”
Section: Ligature-induced Periodontitis Modelmentioning
confidence: 99%
“…In this context, Atorvastatin (ATV) stands out due to its pleiotropic effects [7]. Our group has shown that systemic ATV has antiin ammatory and anti-resorptive effects in experimental periodontitis in rats [8,9] as well as in animals submitted to glucocorticoid-induced osteoporosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies concluded that statin have an anabolic effect on bone [29] . Animal studies showedthat when statin applied locally give good bone regeneration [30][31][32] and enhance new bone formation and bone to implant contact [33] .…”
Section: Introductionmentioning
confidence: 99%